THE EFFECT OF BRAND AMBASSADOR AND CELEBRITY ENDORSER ON CONSUMER PURCHASE INTEREST OF LE MINERALE ON STUDENTS FACULTY OF ECONOMICS, MERDEKA UNIVERSITY, PASURUAN - Akramiah, Nurul; Hastari, Sri; Maulana Sari , Isny (Dinasti International Journal of Digital Business Management, 2021)
Businesspeople are aware of the intense competition as evidenced by the many innovative products that have emerged. It requires companies to develop all aspects of business support, one of which is a marketing strategy. Communicating products through influencers, such as brand ambassadors and celebrity endorsers, is considered adequate to increase customer purchase interest for the sake of survival and competition in an increasingly complex business industry. This study aims to determine the simultaneous and partial effect of brand ambassador and celebrity endorser variables on customer purchase interest in Le Minerale products. In this study, researchers used quantitative methods with an associative approach. The population of this research is all active students of the Faculty of Economics, Merdeka University, Pasuruan, with a total sample of 65 people taken by purposive sampling technique. With the use of multiple linear regression analysis techniques. Based on simultaneous testing, the brand ambassador and celebrity endorser variables jointly have a significant effect on customer purchase interest. Based on the partial test, the brand ambassador variable has a significant effect on customer purchase interest, and the celebrity endorser variable has a significant effect on customer purchase interest. While the value of R Square shows that the brand ambassador and celebrity endorser variables can explain the customer purchase interest variable by 43%, while the remaining 57% is influenced and explained by other factors not examined in this study.